Peat Leith, Kevin O'Toole, Marcus Haward and Brian Coffey, Enhancing Science Impact: Bridging Research, Policy and Practice for Sustainability. (1st October 2019) - Hanke, Annika
Instead of drawing out exact paths for overcoming barriers, the authors of the book Enhancing Science Impact refer back to the necessity of reflecting on all aspects of research. There is no one-fits-all solution of approaching sustainability. Instead a comprehensive understanding of problem-structuring is necessary for addressing current challenges. Even though the work provides a practical foci-guideline, a critical reflection on how nature is represented within research programmes and projects is missing.